2021
DOI: 10.1093/jnci/djab179
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence System for the Detection of Bladder Cancer via Cystoscopy: A Multicenter Diagnostic Study

Abstract: Background Cystoscopy plays an important role in bladder cancer (BCa) diagnosis and treatment, but its sensitivity needs improvement. Artificial intelligence has shown promise in endoscopy, but few cystoscopic applications have been reported. We report a Cystoscopy Artificial Intelligence Diagnostic System (CAIDS) for BCa diagnosis. Methods In total, 69,204 images from 10,729 consecutive patients from six hospitals were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Wu et al found that their AI Algorithm was superior to expert urologists in the detection of complex lesions such as CIS and very small lesions. 68 Further prospective studies are needed to determine incorporation of AI in clinical practice and its use in different patient populations.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Wu et al found that their AI Algorithm was superior to expert urologists in the detection of complex lesions such as CIS and very small lesions. 68 Further prospective studies are needed to determine incorporation of AI in clinical practice and its use in different patient populations.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…A recent study by Wu et al conducted an extensive study incorporating the cystoscopic images of 10 729 patients from 6 different centres. 85 They proposed an algorithm based on a pyramid pooling module, allowing the utilization of information gathered from both the whole image and small areas within the image. Moreover, they trained their algorithm with the help of the large dataset of cystoscopy images and Im-ageNet, and the model was able to achieve accuracies ranging from 97.8 to 99.1% on different external validation sets.…”
Section: Cystoscopy and Aimentioning
confidence: 99%
“…Summarizing its global research trends and research hotspots are of great significance to the next research. Our research team also conducted some AI research in the field of urogenital neoplasms (26)(27)(28). However, there is no research on bibliometric analysis to summarize.…”
Section: Introductionmentioning
confidence: 99%